2022
DOI: 10.3390/ma15093256
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Aging of Epoxy Biocomposites Filled with Cellulose

Abstract: From the 19th century to the present day, rail transport has played a key role in the transportation of goods and passengers [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Finally, the intense peak at approximately 825 cm −1 is due to the presence of C-C stretching vibrations of the epoxy ring (purple highlight). Similar moieties are present in other epoxy resin structures [30]. During the aging process, the new bands at approximately 1725 cm −1 appear as a result of the oxidation process, where carbonyl groups are formed.…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir) Absorbance S...supporting
confidence: 52%
See 1 more Smart Citation
“…Finally, the intense peak at approximately 825 cm −1 is due to the presence of C-C stretching vibrations of the epoxy ring (purple highlight). Similar moieties are present in other epoxy resin structures [30]. During the aging process, the new bands at approximately 1725 cm −1 appear as a result of the oxidation process, where carbonyl groups are formed.…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir) Absorbance S...supporting
confidence: 52%
“…There is a great need for novel pro-ecological materials in different sectors, including the railway industry. For example, increased attention is being paid to the development of novel biocomposites for seats, which should be lightweight and durable [30]. In modern railways, the heavy and expensive metal parts of seats have been replaced with polymer composites, including materials made of epoxy resin, with desirable mechanical properties [31].…”
Section: Introductionmentioning
confidence: 99%
“…New possibilities for applying modified epoxy resin to cement mortars are described [ 21 , 22 ]. A significant branch of the industry where epoxy resins are used is public transport, including the railway industry [ 23 ]. In modern railways, metal parts of seats have been replaced with polymer composites, including materials based on epoxy resin, which have appropriate mechanical properties [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In modern railways, metal parts of seats have been replaced with polymer composites, including materials based on epoxy resin, which have appropriate mechanical properties [ 24 ]. Due to climatic conditions (UV radiation and variable temperatures), epoxy polymer compositions used as seats require stabilization [ 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin belongs to a group of thermosetting polymers that are commonly used in engineering applications due to their high performance (excellent mechanical properties, high thermal and corrosion resistance, etc.) and versatility [ 2 , 3 , 4 , 5 ]. It is reported that approximately 323,000 tons of epoxy resin are produced annually, of which 45,000 tons are used in the transportation industry (14%) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%